2016
DOI: 10.2147/ppa.s112750
|View full text |Cite
|
Sign up to set email alerts
|

Age-related hearing loss in individuals and their caregivers: effects of coping on the quality of life among the dyads

Abstract: ObjectivesAge-related hearing loss (ARHL) impacts the daily living and quality of life (QoL) of affected individuals and the functioning of family caregivers. In the specific context of voluntary medical checkups, we examined sample dyads (ARHL individual and the caregiver) to determine whether QoL of patients and caregivers is influenced by coping strategies implemented either by themselves or their relatives.MethodsThis was a cross-sectional study with a descriptive/correlative design performed in a French p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…The main finding of this study indicates that the QoL of a patient with a newly diagnosed high-grade glioma, assessed away from the diagnosis, may be related not only to the coping strategy he/she mobilizes at the time of diagnosis but also to the coping strategies his/her caregivers mobilize. This observation was already described in cross-sectional studies in both the context of cancer [ 14 , 29 , 30 ] and various non-cancer related contexts [ 16 , 17 , 31 , 32 ]. However, to our knowledge, no study has reported this phenomenon across longitudinal designs that nonetheless allow for causality inferences to be made between coping strategies and QoL.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The main finding of this study indicates that the QoL of a patient with a newly diagnosed high-grade glioma, assessed away from the diagnosis, may be related not only to the coping strategy he/she mobilizes at the time of diagnosis but also to the coping strategies his/her caregivers mobilize. This observation was already described in cross-sectional studies in both the context of cancer [ 14 , 29 , 30 ] and various non-cancer related contexts [ 16 , 17 , 31 , 32 ]. However, to our knowledge, no study has reported this phenomenon across longitudinal designs that nonetheless allow for causality inferences to be made between coping strategies and QoL.…”
Section: Discussionsupporting
confidence: 66%
“…Overall, at the time of the assessment, both mobilized active strategies based on problem-solving and positive thinking more than passive strategies based on looking for social support or avoidance. This trend, already described in the literature in other models of illness [ 15 – 17 ], was always present at the second assessment, 3 months following the diagnosis, during which a sequence of serious events occurs: information about poor prognosis, initiation of the first aggressive treatments, occurrence of serious adverse events due to the treatments, aggravation of disease symptoms, and possible progression of the disease. Because of the rapid progression of the disease, patients with high-grade gliomas and their caregivers only have a short time to adapt.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In particular, patients and their caregivers were found to implement coping strategies based on problem solving and positive thinking more than strategies based on social support or avoidance (statistically not tested). This unbalanced use has already been described in other populations, including individuals with severe and less severe diseases and impairments, such as gliomas, depression, and age‐related hearing loss, and their caregivers. This finding suggests that people who know each other very well and who face the same difficult situation tend to cope with it similarly.…”
Section: Discussionmentioning
confidence: 74%
“…In the specific context of ARHL, we previously emphasized [19] that quality of life of individuals and their natural caregivers was related to the coping strategies that they use. However, the previous study was performed on a small sample size ( N = 44) and did not use specific dyadic analyses that integrate a conceptual view of interdependence in two-person relationships.…”
Section: Introductionmentioning
confidence: 99%